Ecotourism Glocalization: An Analysis of Policy and Expert Perspectives. Issue 3 (4th May 2021) - Cobbinah, Patrick Brandful; Black, Rosemary; N-yanbini, Nelson Nyabani
ABSTRACT: This paper presents a set of four derived attributes that define and operationalize the concept of ecotourism. Using these four attributes, data collection focused on interviews with officials and tour operators from 25 ecotourism agencies in Ghana, and analysis of six most recent and relevant national tourism documents to determine how congruent the documents reflected the practice of ecotourism. Findings indicated variations in understandings of the ecotourism concept amongst ecotourism officials, with national tourism documents in some cases stating various intentions to implement ecotourism. The analysis showed a disconnect between these national tourism documents and the implementation and practice of ecotourism as ecotourism actions are not consistent with the provisions in the tourism documents, and implementation strategies are lacking. A number of local factors emerged from the interviews as contributors: land tenure uncertainties, seasonal fluctuation of demand, commodification, and limited capacity building. Recommendations to improve the situation are proffered.